The impact of telemedicine services on primary health care - before and after analysis- Jharkhand digital dispensary model - Das, Santos; Kosuru, Akhila; Maran, Tamil; Thaploo, Vikram (International Journal Of Community Medicine And Public Health, 2023)
Background: The service utilization at primary health cares (PHCs) by the rural population is challenging considering the lack of service availability and health care practitioners. Telemedicine and digitization of services have high potential to address the service provision gaps. Government of Jharkhand and Apollo tele health services-initiated PPP project to provide digital healthcare (digital dispensary) services at 100 rural PHCs in the state of Jharkhand. Methods: The research study seeks to explore before and after impact of telemedicine services at the government run PHCs at Jharkhand. This retrospective analysis of health management information system (HMIS) and Jharkhand digital dispensary (JHDD) project data was performed for 19 PHCs out of 100 where JHDD project has been initiated. A pre-post study design was used to understand the impact of JHDD project implementation and uptake of outpatient department (OPD) utilization. The 19 centers were randomly selected using selective sampling, considering the data availability and travelling restrictions. Primary baseline data was analyzed in the excel sheet and secondary data- was entered, verified, and analyzed with statistical package for the social sciences (SPSS) version 25. Results: Patients have to travel up to 75 kms to visit a doctor and avail health services. Medical officer was adequate, but not available for eight hours and every day. JHDD project data have highlighted the prevalence of NCDs in rural areas with significant increase in the diagnosis of diabetes and hypertension. The availability of general physician and specialist doctors virtually, with laboratory tests and medicines were the enabling factors in addressing the NCDs for the rural areas. Conclusions: Telemedicine is strong enabler in addressing NCDs in remotest inaccessible areas. The study has pointed out the importance of available remote workforce, basic infrastructure and technology can strengthen the healthcare system by reaching the unreached.